AVALIAÇÃO ULTRA-SONOGRÁFICA DO FETO E DO MEIO INTRA-UTERINO DURANTE O ÚLTIMO MÊS DE GESTAÇÃO EM ÉGUAS PURO SANGUE INGLÊS (PSI) - TULLIO, D.M.; KOZICKI, L.E.; SILVA, A.W.C. (Archives of Veterinary Science, 2004)
Com o objetivo de avaliar o diâmetro da aorta fetal, freqüência cardíaca fetal, atividade fetal, ecogenicidade dos líquidos alantóide amniótico e espessura da unidade feto-placentária, trinta e oito éguas Puro-Sangue Inglês (PSI) com gestações saudáveis foram examinadas por ultra-sonografia. O valor médio da freqüência cardíaca fetal variou de 73,05 ± 2,99 bat/min aos 300-330 dias de gestação para 70,05 ± 1,88 bat/min a partir de 330 dias de gestação. O valor médio do diâmetro da aorta fetal foi 23,69 ± 1,66 mm e a média da atividade fetal foi 2,03 ± 0,19. A espessura da unidade feto-placentária apresentou valores médios de 8,70 ± 0,92 mm para 300-330 dias, e 9,57 ± 0,49 mm para 330 dias até o parto. O valor médio para a ecogenicidade do líquido amniótico foi 1,96 ± 0,27, e para o líquido alantóide foi 1 ± 0. Ultrasonographic evaluation of the fetus and intrauterine environment in the last month of pregnancy in thoroughbred mares Abstract Thirty eight thoroughbred mares with normal pregnancies were subjected to transabdominal and transrectal sonography from 300 days of gestation up to the term in order to evaluated fetals aortic diameter, heart rate and activity, as well as the amniotic and allantoic fluids ecogenicity and the thickness of the uterus and placenta unit. The mean fetal heart rate values varied from 73,05 ± 2,99 beats/minute at 300-330 days of pregnancy to 70,05 ± 1,88 beats/minute from 330 days of pregnancy up to the term. The mean value for fetal aortic diameter was 23,69 ± 1,66 mm and for fetal activity was 2,03 ± 0,19. The uterus and placenta thickness displayed mean values of 8,70 ± 0,92 mm and 9,57 ± 0,49 mm at 300-330 days of pregnancy mm and at 330 days of pregnancy up to the term, respectively. The mean values for amniotic fluid ecogenicity and for allantoic fluid were found to be 1,96 ± 0,27 and 1,0, respectively. These evaluations can be used as normal values in order to evaluate fetal well-being.